Meta-service Design and Implementation for Content Delivery Network Cloud Environments - Xiaoying Wang; Xin Jin; Lihua Fan; Weitong Huang (Institute of Advanced Engineering and Science, 2012)
Storage has emerged as a typical kind of service in the cloud environment as the content delivery network (CDN) emerges and becomes widely-used. In this paper, we conducted a research on the management issues for such applications, and implemented some meta-services upon the underlying cloud services. The architecture of the system was described in detailed and the detailed design of four types of meta-services was further discussed. The implementation of the key components was presented one by one, depicting the functionalities of these meta-services. Experimental results show that the implemented prototype can work effectively and meaningful suggestions could be given according to users’ requests, and thus exhibit the advantages of employing the proposed meta-services. Moreover, by presenting a special case study, the feasibility and usability of meta-services in the CDN is further illustrated. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1582